2019
DOI: 10.1155/2019/6471815
|View full text |Cite
|
Sign up to set email alerts
|

Louqin Zhisou Decoction Inhibits Mucus Hypersecretion for Acute Exacerbation of Chronic Obstructive Pulmonary Disease Rats by Suppressing EGFR-PI3K-AKT Signaling Pathway and Restoring Th17/Treg Balance

Abstract: Airway mucus hypersecretion is the main pathogenic factor in acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and the control of mucus secretion is closely associated with survival. Louqin Zhisou decoction (LQZS) has been found to improve lung function and reduce sputum in AECOPD patients, but the mechanism remains unclear. This study aimed to explore the mechanism of LQZS against mucus hypersecretion in lung tissues of rat AECOPD model. Wistar rats were used to establish AECOPD model by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Components of cigarette smoke and respiratory pathogens activate Akt through cell surface receptors on alveolar macrophages and the bronchial epithelium. Consistent with Akt activation in human COPD, increases in Akt phosphorylation has been observed in the lungs of rat models of COPD and acute exacerbation of chronic obstructive pulmonary disease (AECOPD) [43][44][45]. However, cigarette smoke extract has also been reported to induce Akt degradation via TTC3, a ubiquitin ligase, in human lung fibroblasts [46], suggesting that Akt levels and activity are tightly regulated in COPD.…”
Section: Discussionmentioning
confidence: 89%
“…Components of cigarette smoke and respiratory pathogens activate Akt through cell surface receptors on alveolar macrophages and the bronchial epithelium. Consistent with Akt activation in human COPD, increases in Akt phosphorylation has been observed in the lungs of rat models of COPD and acute exacerbation of chronic obstructive pulmonary disease (AECOPD) [43][44][45]. However, cigarette smoke extract has also been reported to induce Akt degradation via TTC3, a ubiquitin ligase, in human lung fibroblasts [46], suggesting that Akt levels and activity are tightly regulated in COPD.…”
Section: Discussionmentioning
confidence: 89%
“…The EGFR structure comprises three parts: the extracellular glycosylated ligand recognition domain, a hydrophobic transmembrane segment, and the intracellular portion containing a highly conserved tyrosine kinase sequence [ 28 ]. After transactivation, EGFR stimulates downstream signaling cascades to protect cells or to promote cell growth [ 10 , 31 , 32 ]. PI3K/AKT is one of the most representative signaling pathways activated after phosphorylation of EGFR [ 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of this pathway promotes trophoblast apoptosis and suppresses trophoblast proliferation and migration [ 33 , 34 ]. This pathway also controls the differentiation of Treg and Th17 cells [ 35 ]. We found that the phosphorylation level of AKT in the placentas of ACA-positive pregnant mice was increased significantly, while it was decreased by AZHJ.…”
Section: Discussionmentioning
confidence: 99%